Prevalence and epidemiology of presumptive cerebral microbleeds in a population of 747 dogs undergoing brain MRI: a retrospective study - Cássia Maria Molinaro Coelho; Gabriela Wacheleski Brock; Roberta Amaral Ferraz Barros; Alex Gradowski Adeodato; Mauro Caldas Martins; Tais Ferreira Guimarães; Gabriela Carvalhaes Potgieter; Lucas Rego Ramos; Marcos Fabio DosSantos (PLoS ONE, 2025)
Current advances in veterinary medicine have led to a significant increase in the longevity of dogs, and age-related brain changes have become more recognized, such as cerebral microbleeds (CMBs). However, few studies have described their occurrence and epidemiology in dogs. This retrospective study describes the signalment and MRI findings in dogs with presumptive CMBs (pCMBs) and their association with concurrent age-related changes. A database of exams obtained from a veterinary MRI diagnostic center was reviewed. Signalment information such as breed, age, sex, and concurrent MRI findings were evaluated and compared between groups. A total of 747 dogs that underwent 1.5T brain MRI with standard sequences (T2, FLAIR, T1, and T2*) were included. A total of 142 dogs (19%) met the inclusion criteria for pCMBs. The prevalence of pCMBs increased with age, especially in those older than ten years. Small breed dogs were significantly more affected than large-breed dogs. Female dogs showed higher prevalence than males, likely related to longer lifespan. Most dogs had multiple pCMBs (62%), mainly with a lobar distribution (57.7%). Brain atrophy was significantly identified concurrently with pCMBs in 61.3% of the dogs. The results of the current study support that pCMBs constitute a common age-related MRI finding in small-breed dogs and females, frequently associated with brain atrophy.